If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -5)(x + 4) = (x + 7)(x + -6) Reorder the terms: (-5 + x)(x + 4) = (x + 7)(x + -6) Reorder the terms: (-5 + x)(4 + x) = (x + 7)(x + -6) Multiply (-5 + x) * (4 + x) (-5(4 + x) + x(4 + x)) = (x + 7)(x + -6) ((4 * -5 + x * -5) + x(4 + x)) = (x + 7)(x + -6) ((-20 + -5x) + x(4 + x)) = (x + 7)(x + -6) (-20 + -5x + (4 * x + x * x)) = (x + 7)(x + -6) (-20 + -5x + (4x + x2)) = (x + 7)(x + -6) Combine like terms: -5x + 4x = -1x (-20 + -1x + x2) = (x + 7)(x + -6) Reorder the terms: -20 + -1x + x2 = (7 + x)(x + -6) Reorder the terms: -20 + -1x + x2 = (7 + x)(-6 + x) Multiply (7 + x) * (-6 + x) -20 + -1x + x2 = (7(-6 + x) + x(-6 + x)) -20 + -1x + x2 = ((-6 * 7 + x * 7) + x(-6 + x)) -20 + -1x + x2 = ((-42 + 7x) + x(-6 + x)) -20 + -1x + x2 = (-42 + 7x + (-6 * x + x * x)) -20 + -1x + x2 = (-42 + 7x + (-6x + x2)) Combine like terms: 7x + -6x = 1x -20 + -1x + x2 = (-42 + 1x + x2) Add '-1x2' to each side of the equation. -20 + -1x + x2 + -1x2 = -42 + 1x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -20 + -1x + 0 = -42 + 1x + x2 + -1x2 -20 + -1x = -42 + 1x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -20 + -1x = -42 + 1x + 0 -20 + -1x = -42 + 1x Solving -20 + -1x = -42 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -20 + -1x + -1x = -42 + 1x + -1x Combine like terms: -1x + -1x = -2x -20 + -2x = -42 + 1x + -1x Combine like terms: 1x + -1x = 0 -20 + -2x = -42 + 0 -20 + -2x = -42 Add '20' to each side of the equation. -20 + 20 + -2x = -42 + 20 Combine like terms: -20 + 20 = 0 0 + -2x = -42 + 20 -2x = -42 + 20 Combine like terms: -42 + 20 = -22 -2x = -22 Divide each side by '-2'. x = 11 Simplifying x = 11
| 3w+7=-6.4 | | 2k=-f-t | | 7-2x(x+4)=14+5x | | t=2k-f | | p=b+2d | | 3x*4x=600 | | 3x*4X=24 | | 7x+21y=28 | | 2x+4=-8-4x | | 2x-x+30=80 | | 2x*5+6=3 | | 2x*11=3 | | 750*1300= | | 14*2x+24*8-9=52*13+121*11 | | 90x^2-97xy+21y^2=0 | | 5678=10131213 | | 8x-6x+3=2 | | 2b+7=b+13 | | 15x+21y=261 | | 9v+27=-2(v+3) | | F(x-1)=10x-6 | | 55=9x | | 14+n=-9 | | 2x-(2+3)=5x | | 3x+15x-2x+3=15x+1x+3 | | 5p=42 | | 4(2e+3)=7e+2 | | Y-9.74=3.25 | | (3x+7y)=(4x-5y) | | 5x^2+8x+110=0 | | 7x^2-11y^2=11 | | 7x^2-11y^2=10 |